Control of redundant robots under end-effector commands: A case study in underactuated systems - Luca, Alessandro de; Mattone, Raffaella; Oriolo, Giuseppe (Zielona Góra: Uniwersytet Zielonogórski)
We analyze the control problem for a kinematically redundant robot driven by forces/torques imposed on the end-effector, an interesting example of underactuated system. A convenient format for the dynamic equations of this mechanism can be obtained via partial feedback linearization. In particular, we point out the existence of two special forms in which the system can be put under suitable assumptions, namely the second-order triangular and Caplygin forms.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka